2016
DOI: 10.1186/s40064-016-2477-x
|View full text |Cite
|
Sign up to set email alerts
|

Parametric investigation on mixing in a micromixer with two-layer crossing channels

Abstract: This work presents a parametric investigation on flow and mixing in a chaotic micromixer consisting of two-layer crossing channels proposed by Xia et al. (Lab Chip 5: 748–755, 2005). The flow and mixing performance were numerically analyzed using commercially available software ANSYS CFX-15.0, which solves the Navier–Stokes and mass conservation equations with a diffusion–convection model in a Reynolds number range from 0.2 to 40. A mixing index based on the variance of the mass fraction of the mixture was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…As can be seen from Table 3, when Re < 10, all the mixers could work. When Re < 1, more than half of the mixers worked (the mixers in references [11,12,13,14,24,26] and the mixer used in this paper), which indicated that these devices were suitable for laminar flow mixing. For all the mixers, the maximum mixing length was no more than 13 mm [12], while the minimum mixing length was 2.75 mm [11], which indicated that the structure size was suitable for integration in μTASs.…”
Section: Resultsmentioning
confidence: 78%
See 2 more Smart Citations
“…As can be seen from Table 3, when Re < 10, all the mixers could work. When Re < 1, more than half of the mixers worked (the mixers in references [11,12,13,14,24,26] and the mixer used in this paper), which indicated that these devices were suitable for laminar flow mixing. For all the mixers, the maximum mixing length was no more than 13 mm [12], while the minimum mixing length was 2.75 mm [11], which indicated that the structure size was suitable for integration in μTASs.…”
Section: Resultsmentioning
confidence: 78%
“…The mixing index of each mixer exceeded 70%. However, for seven mixers, the mixing index exceeded 80% (the mixers in references [11,13,14,15,24,26], and for three mixers, it exceeded 90%, namely the GSMMT (grooves staggered in the upper and lower layers at the midstream positions) [15] ( α = 90%, when Re = 96), the 3D Tesla [13] ( α = 94%, when Re = 1), and the 3D HT used in the present study ( α simulation = 96.4%, α test = 91.75%, when Re = 10). However, compared to the 3D HT mixer, the GSMMT structure required a higher Re, while the 3D Tesla needed more mixing units to ensure mixing efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A mixing index of 0.96 was obtained for Re=0.2. In a recent paper, Hossain et al [18] characterized the mixing performance of Newtonian fluids in two-layer crossing channels micromixer for Reynolds number ranging from 0.2 to 40. Their results outline that the mixing index reached 0.90 with variations of the geometric parameters even at creeping flow, Re = 0.2.…”
Section: Introductionmentioning
confidence: 99%
“…Active mixers require an external input, e.g., acoustics, electricity, or magnetic fields implying complex off‐chip setups. Passive mixers cause mixing by structural features inside the microfluidic channel that stretch and fold the liquids to induce shorter path lengths for diffusion . One particular example is the slanted groove mixer, consisting of a microchannel with a grooved wall.…”
Section: Introductionmentioning
confidence: 99%